(untitled) (Bangladesh Critical Care Journal, 2026)
Background: Ischaemic dilated cardiomyopathy (IDCM) is a well-recognised consequence of coronary artery disease (CAD), characterised by ischaemia-induced ventricular remodelling, which leads to irreversible myocardial tissue loss and impaired contractility, predominantly affecting left ventricular ejection fraction. In view of the high prevalence of chronic heart failure due to underlying IDCM and the lack of data on IDCM, this study was undertaken. Objective: The objective of this retrospective cross sectional study was done to find out the incidence, severity and echocardiographic findings in patients having Ischaemic Dilated cardiomyopathy. Methods: Retrospective cross sectional observational study was conducted in the Department of Cardiology in BIRDEM General Hospital, Dhaka, Bangladesh which is a tertiary care hospital in Dhaka & attached with Ibrahim Medical College. Secondary data was collected from July, 2020 to June, 2024. All patients who attended Echocardiography room of cardiology department in BIRDEM General Hospital and found to have Echocardiographic findings of IDCM were included in this study. Purposive sampling method was applied as per availability and satisfying the inclusion and exclusion criteria. Results: Fifty eight thousand two hundred and twenty seven (58,227) ecocardiography were done and 663 patients were diagnosed as IDCM. Among them, 440 (66.4%) were male and 223 (33.6%) were female with mean age 57.41 years. Regarding severity of Ejection fraction, most patients were in the range 30-39%, the next was between 20-29% and the lowest was<20%. Regarding echocardiographic parameters in IDCM, dilatation of left ventricle (both LVIDd and LVIDs) was invariably present in almost all patients. Enlargement of LA was found in 61.38% and RV was present in 78.58%. Regarding valvular regurgitation in IDCM, mitral regurgitation was the commonest which was present in 92.8% cases where moderate regurgitation dominating at 54.9%, followed by mild (32.1%) and a smaller but clinically important group with severe involvement (5.7%). Tricuspid regurgitation was present in 76.9% cases, pulmonary regurgitation in 44% cases and aortic regurgitation in 33.3 % cases. The highest proportion of RV dysfunction was recorded in 2024, with 137 out of 196 patients. The majority had no effusion, accounting for 512 patients (77.2%). Mild effusion was observed in 87 patients (13.1%), while moderate effusion was present in 56 patients (8.4%). Severe effusion was the least common finding, seen in only 8 patients (1.2%). The analysis showed that patients older than 50 years had significantly larger chamber dimensions. Right ventricular internal dimension at end-diastole, left ventricular internal diameter at end-diastole, and left ventricular internal diameter at end-systole were all significantly higher in the older group (p=0.025, p=0.042, and p=0.032, respectively). Conclusion: This study identifies the increasing frequency of IDCM, which occurs mainly in the elderly with increased prevalence in men. Incidence of IDCM was 1.13 % over 5 years. The largest population of participants were within age range 40-60 years. Diabetes Mellitus and HTN were common risk factor. Bangladesh Crit Care J March 2026; 14 (1): 16-22